An injectable curcumin-releasing organohydrogel with non-drying property and high mechanical stability at low-temperature for expedited skin wound care. (10th January 2023) - Wu, Kang; Yang, Qiang; Zhang, Lin; Xu, Pengcheng; Wu, Xiexing; Yang, Huilin; Zhou, Huan; Lin, Xiao; Yang, Lei
Highlights: An injectable organohydrogel (IOH) is developed for expedited skin wound care. IOH has non-drying property and high mechanical stability at low-temperature. IOH demonstrated an efficient loading and sustained release of curcumin. Curcumin-releasing IOH enhanced healing of a murine full-thickness defect wound. Abstract: Although hydrogels have demonstrated great potential as new wound dressing materials, their instability in shape and/or mechanical characteristics due to water loss or freezing remains a shortcoming for wound care application. Herein, a novel injectable organohydrogel (IOH) of physically crosslinked polyvinyl alcohol/glycerol that possesses non-drying capability and high stability at low temperature was developed for wound care. IOH has a skin-like stiffness ( G', ∼280 Pa), high injectability, self-healing capability, high water-vapor transmission rate, and bacterial inhibitory effect. IOH exhibits high shape and mechanical stabilities after curing at 37 °C and 50% relative humidity for 7 days or after curing at –20 °C for 1 day. In addition, glycerol in IOH enabled an efficient loading and release of water-insoluble curcumin, a well-known anti-bacterial and anti-inflammation drug. The curcumin-releasing IOH (Cur-IOH) demonstrated significantly enhanced anti-bacterial performance compared to IOH or curcumin-loading polyvinyl alcohol hydrogel. More importantly, Cur-IOH could accelerate wound healing in a murine full-thickness skin defect wound model, revealing improved wound contraction, collagen deposition, angiogenesis, and epidermis formation. This study demonstrates the great potential of organohydrogel for the reparation of severe wounds and Cur-IOH as a new type of injectable wound healing material. Graphical abstract: Image, graphical abstract